2013
DOI: 10.4236/am.2013.48a008
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Biomass Production of Haematococcus pluvialis

Abstract: Microalgae cultivation is justified by the production of high-value fine chemicals and biofuels, essential to reduce the emissions of gases that cause global warming. This paper presents a study of the growth of microalgae Haematococcus pluvialis considering light conditions from 2000 to 10,000 lux, temperature 22˚C and pH in the 6.5 -12.5 range. The experiments were performed in 4 liter flat plate photobioreactors using the Rudic culture medium. The biomass growth was measured by counting cells in a Neubauer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
7
0
4
Order By: Relevance
“…The optimized biomass concentrations and maximum productivity for the hybrid ANN were 10% and 40%, respectively, higher than those predicted by the deterministic kinetic model [65]. Likewise, Galvão et al [94] investigated the influence of pH on biomass concentration using ANN and indicated that the neural network model was able to efficiently predict the process output. The aforementioned reports and other studies on the use of ANNs for optimization of biomass concentration for microalgae biodiesel production are summarized in Table 4.…”
Section: Microalgae Biodiesel Productionmentioning
confidence: 99%
“…The optimized biomass concentrations and maximum productivity for the hybrid ANN were 10% and 40%, respectively, higher than those predicted by the deterministic kinetic model [65]. Likewise, Galvão et al [94] investigated the influence of pH on biomass concentration using ANN and indicated that the neural network model was able to efficiently predict the process output. The aforementioned reports and other studies on the use of ANNs for optimization of biomass concentration for microalgae biodiesel production are summarized in Table 4.…”
Section: Microalgae Biodiesel Productionmentioning
confidence: 99%
“…Kinetic models serves in designing a bioreactor, controlling the microbial processes and predicting the behavior of the processes more easily than laboratory experiments (Bailley and Ollis 1986 ). To learn the dynamics of biomass growth and lipid production by microalgae, suitable kinetic modeling has to be developed for predicting the performance and optimization of photobioreactor operating conditions (Galvao et al 2013 ). Many research studies have been conducted and many mathematical models proposed for microalgal growth and lipid production.…”
Section: Introductionmentioning
confidence: 99%
“…A influência do pH sobre o crescimento celular foi verificada no décimo dia de cultivo onde ocorreu a maior variação de pH (7,4) ocorrendo maior concentração celular (1,13 g.L -1 ). Esse comportamento é esperado, pois, de acordo com Galvão et al (2013), normalmente a microalga H. pluvialis entra em estado de excitação em pH mais baixos, passando a produzir mais pigmento. Sarada, Bhattacharya e Ravishankar (2002) relatam que, para a mesma microalga, o pH ótimo para produção de biomassa e astaxantina está na faixa de 7,0-7,8.…”
Section: Resultsunclassified
“…As microalgas, por serem fotossintéticas, absorvem e utilizam CO 2 como a principal fonte de carbono no crescimento celular. Logo, a biossíntese de carotenoides pode ocorrer pela limitação do nitrogênio em presença de excesso de fontes de carbono, como a utilização de CO 2 ou acetato e glicose em cultivos mixotróficos (GALVÃO et al, 2013).…”
Section: Introductionunclassified